Large‐Area van der Waals Epitaxial Growth of Vertical III‐Nitride Nanodevice Structures on Layered Boron Nitride. Issue 16 (19th June 2019) - Sundaram, Suresh; Li, Xin; Halfaya, Yacine; Ayari, Taha; Patriarche, Gilles; Bishop, Christopher; Alam, Saiful; Gautier, Simon; Voss, Paul L.; Salvestrini, Jean Paul; Ougazzaden, Abdallah
Abstract: Hexagonal boron nitride (h‐BN) is a promising 2D template that decouples substrate effects from the layer above it by van der Waals epitaxy, because there are only weak forces out of the h‐BN. It also permits convenient mechanical transfer of devices grown on their surface to an appropriate substrate. Here, van der Waals epitaxial growth resulting in the formation of self‐organized GaN nanorods on h‐BN templates is demonstrated. This approach to the growth of III‐N nanostructures avoids transfer processes and scaling issues seen with other 2D materials, since both the 1D (GaN nanorods) and 2D (h‐BN) are grown at the wafer‐scale and in one growth run. Further, this process is used to grow vertical core–shell p‐GaN/InGaN/n‐GaN nano‐PIN device structures on wafer‐scale 2D h‐BN on sapphire and silicon substrates. The high quality of the core–shell nanostructures is confirmed by detailed electron microscopy study, which gives more insight into the nanorod formation mechanism on 2D material. Mechanical transfer of nanostructures on sapphire substrates to copper tape is then demonstrated, with no resulting damage of nanorods. Use of MOVPE grown large‐area h‐BN to realize nanostructures is a significant advancement and can lead to new nanodevice architectures needed for next‐generation optoelectronic devices. Abstract : Van der Waals epitaxial growth resulting in the formation of self‐organized GaN nanorods on layered hexagonal boron nitride (h‐BN) templates is demonstrated. This approach is used to grow III‐N nanowire light‐emitting diodes, and it avoids transfer processes and scaling issues seen with other 2D materials, since both the 1D (GaN nanorods) and 2D (h‐BN) are grown at the wafer‐scale and in one growth run.